Conceptual Provisions of Management Modeling in the System of Strategic Management of Enterprise Development - Ivaniuk, Ulana V.; Halaz, Lina V. (Bìznes ìnform (Multilingual ed.), 2024)
The article updates the issue of ensuring the stable functioning and development of economic entities on the basis of proper strategic management, planning and modeling in the system of strategic business management. The aim of the study is to generalize and further develop the conceptual foundations and provisions of management modeling in the system of strategic management of enterprise development. It has been proven that in order to guarantee stable long-term functioning, enterprises and organizations should use management modeling tools in the system of strategic management of the development of the economic entity. It is found that the main subjects of management analysis are strategic goals and tasks, in particular for key functional areas of business: finance, marketing, production, commercial and sales activities, personnel management, investments, innovations, etc. As noted in the study, this is a compromise between ensuring adequate financial stability, liquidity and solvency, a high level of profitability, rentability, capitalization and reinvestment, on the one hand, and meeting the main requirements and needs of consumers of products (goods, works, services), on the other hand. It is determined that the quality toolkit of management modeling in the system of strategic management of the development of the business entity in terms of finance and marketing involves the management of financial goals and objectives, financial variables, decisions in the field of marketing and logistics, expectations of buyers, marketing objectives. It is summarized that strategic orientations and objectives serve as a starting point during planning, forecasting, modeling of important parameters – criteria for stable functioning and development of the economic entity. In turn, the leading aspects of the organization's development strategizing are determined using management modeling tools. It is pointed out that the promising direction of further research in this area is the improvement of the methodology of analyzing the quality of strategic management of economic entities.